Recombinant human erythropoietin, and myocardial and cerebral acute ischemia: implications for clinical use. - Rafael Alejandro Gómez Baute; Liermis Dita Salabert; Yaney González Yglesias; Tamara Guerra Alfonso; Maritza Cabrera Zamora (Medisur)
Recombinant human erythropoietin has been used for more than two decades in clinical practice with promising results in the treatment of anemia associated with chronic renal insufficiency and in patients with cancer. Recent evidence has uncovered new nonhematopoietic functions of this protein and have brought new hope in the treatment of diseases with ischemic component. In the present review is rife with detail about these new features in the light of new discoveries and explores the therapeutic opportunities offered by these new scientific evidence.